27x(cubed)64
4 Answers

27x^3 – 64 =
(3x)^3 – (4)^3
Now apply this differenceofcubes formula:
a^3 – b^3 = (ab)(a^2 + ab + b^2)
This gives you (3x – 4)(9x^2 + 12x + 16)
Somebody else gave (3x – 4)^3 as an answer, which is just plain wrong. You can’t just distribute the exponent like that. Notice that if you let x=2, then (3x)^3 – (4)^3 = 6^3 – 4^3 = 152, but (3x4)^3 = (64)^3 = 8.
(EDIT: nevermind, they seem to have deleted it)

27x 3 64

(3x)^3 – 4^3
(3x4)(9x^2+12x+16) using a^3 – b^3 = (a – b) (a^2 +ab+b^2)

Booty